2019
DOI: 10.1097/cm9.0000000000000382
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of intermediate-risk to high-risk stage I endometrial cancer

Abstract: Background: There are only very few reports on clinical outcomes using multi-channel applicators (MCA) for patients with endometrial cancer (EC) in China. We aimed to evaluate the clinical experience of treating intermediate-risk (IR) to high-risk (HR) stage I EC using in-house made multi-channel applicators (IH-MCA) in a single institution. Methods: Three hundred and ninety patients with stage I IR to HR EC were treated with hysterectomy and adjuvant radiotherapy from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Endometrial cancer is one of the most common malignancies in postmenopausal women (Moore & Brewer, 2017), and studies have shown that obesity and aging could lead to increased morbidity (Braun, Overbeek-Wager, & Grumbo, 2016;Haggerty et al, 2017). Other risk factors include diabetes, breast cancer, tamoxifen use, unproductiveness, advanced menopause, and exposure to high levels of estrogen (Hou, Yu, Hu, & Zhang, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Endometrial cancer is one of the most common malignancies in postmenopausal women (Moore & Brewer, 2017), and studies have shown that obesity and aging could lead to increased morbidity (Braun, Overbeek-Wager, & Grumbo, 2016;Haggerty et al, 2017). Other risk factors include diabetes, breast cancer, tamoxifen use, unproductiveness, advanced menopause, and exposure to high levels of estrogen (Hou, Yu, Hu, & Zhang, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The results of survival analysis show that only preoperative serum CA125 and age at diagnosis were independent prognostic factors for 5‐year OS with early‐stage EC. The results of previous literatures also proved that preoperative tumor markers such as CA125 and age are prognostic factors for EC 6,7 …”
Section: Discussionmentioning
confidence: 71%
“…Age is another important clinical factor for EC. Our previous results showed that age was an important independent prognostic factor for early‐stage EC and that the disease‐related mortality of patients increased gradually with increasing age 7 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations